Recent Progress in Adipic Acid Synthesis Over Heterogeneous Catalysts - Yan, Wenjuan; Zhang, Guangyu; Wang, Jinyao; Liu, Mengyuan; Sun, Yu; Zhou, Ziqi; Zhang, Wenxiang; Zhang, Shuxia; Xu, Xiaoqiang; Shen, Jian; Jin, Xin (Frontiers in Chemistry, 2020)
Adipic acid is one of the most important feedstocks for producing resins, nylons, lubricants, plasticizers. Current industrial petrochemical process, producing adipic acid from KA oil, catalyzed by nitric acid, has a serious pollution to the environment, due to the formation of waste nitrous oxide. Hence, developing cleaner methods to produce adipic acid has attracted much attention of both industry and academia. This mini-review article discussed advances on adipic acid synthesis from bio-renewable feedstocks, as well as most recent progress on cleaner technology from fossil fuels over novel catalytic materials. Synthetic routes for bio-derived adipic acid will be critically revised, while novel catalytic materials with high atomic efficiency for fossil-derived adipic acid will be discussed and compared. This work on recent advances in green adipic acid production will provide insights and guidance to further study of various other industrial processes for producing nylon precursors.